2013
DOI: 10.4236/msa.2013.46047
|View full text |Cite
|
Sign up to set email alerts
|

Gelation of <i>Antheraea pernyi</i> Silk Fibroin Accelerated by Shearing

Abstract: The rapid manufacture of silk fibroin gels in mild conditions is an important subject in the field of silk-based biomaterials. In this study, the gelation of Antheraea pernyi silk fibroin (ASF) aqueous solution was induced by shearing, without chemical cross-linking agents. Simple shearing controlled and accomplished the steady and rapid conformational transition to β-sheets with ease. The conformational transformation and rapid gelation mechanisms of ASF induced by shearing were tracked and analyzed by circul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Even though it was reported that shearing force could decrease gelation time of SF solution, the effect was significant in SF solution from A. pernyi rather than SF solution from B. mori. Twenty-two to forty-eight hours were needed for SF gelation with shearing for 30-90 minutes at 280-480 rpm [80]. Not only the impractical long period of gelation time is needed, but also massive bubble formation within the solution found after shearing with homogenizer probe makes this method not a suitable way for induction of SF hydrogel for our work.…”
Section: Sterile Production Of Silk Fibroin Solutionmentioning
confidence: 99%
“…Even though it was reported that shearing force could decrease gelation time of SF solution, the effect was significant in SF solution from A. pernyi rather than SF solution from B. mori. Twenty-two to forty-eight hours were needed for SF gelation with shearing for 30-90 minutes at 280-480 rpm [80]. Not only the impractical long period of gelation time is needed, but also massive bubble formation within the solution found after shearing with homogenizer probe makes this method not a suitable way for induction of SF hydrogel for our work.…”
Section: Sterile Production Of Silk Fibroin Solutionmentioning
confidence: 99%